2020
DOI: 10.1101/2020.03.30.017046
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of transcranial direct current stimulation on corticospinal and cortico-cortical excitability and response variability: conventional versus high-definition montages

Abstract: Response variability following transcranial direct current stimulation (tDCS) highlights need for exploring different tDCS electrode montages. This study compared corticospinal excitability (CSE), cortico-cortical excitability and intra-individual variability following conventional and HD anodal (a-tDCS) and cathodal (c-tDCS) tDCS. Fifteen healthy young males attended four sessions at least one-week apart: conventional a-tDCS, conventional c-tDCS, HD-a-tDCS, HD-c-tDCS. TDCS was administered (1mA, 10-minutes) o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
(72 reference statements)
0
4
1
Order By: Relevance
“…This recent work does not include any genotyping, but it does provide the simulation of the applied tDCS montage and the resulting differences in cortical excitability. While no significant effect of the anodal tDCS on the MEP amplitude was found in Pellegrini et al (2021c), a very significant effect was found in the present study (Pellegrini et al, 2021a). The authors do not comment on this discrepancy.…”
Section: Introductioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This recent work does not include any genotyping, but it does provide the simulation of the applied tDCS montage and the resulting differences in cortical excitability. While no significant effect of the anodal tDCS on the MEP amplitude was found in Pellegrini et al (2021c), a very significant effect was found in the present study (Pellegrini et al, 2021a). The authors do not comment on this discrepancy.…”
Section: Introductioncontrasting
confidence: 79%
“…Still, the experiment itself and the statistical analysis deserve some constructive criticism. The experimental design used in this study is based on a recently published manuscript in Neuroscience Research (Pellegrini et al, 2021c). This recent work does not include any genotyping, but it does provide the simulation of the applied tDCS montage and the resulting differences in cortical excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the variance in experimental outcomes in response to tDCS was caused by several factors associated with high inter-individual variability, including the organization of local circuits, basal level of function, psychological state, level of neurotransmitters and receptor sensibility, baseline neurophysiological state, and genetic aspects (López-Alonso et al, 2015 ; Pellegrini et al, 2018a , b ; Machado et al, 2019 ). In addition, those previous studies used different experimental designs and stimulation protocols (i.e., different montages), potentially contributing to the variance in the results or even the reversal effect (Datta et al, 2009 ; Angius et al, 2018 ; Machado, S. et al, 2019 ; Hassanzahraee et al, 2020 ; Pellegrini et al, 2020 ). For example, Hassanzahraee et al ( 2020 ) observed the reversal of corticospinal excitability of anodal tDCS with a current intensity of 1.0 mA when the stimulation duration was over 26 min, which may provide certain implications for preventing excessive brain activation.…”
Section: Discussionmentioning
confidence: 99%
“…For anodal HD-tDCS, the anodal electrode was set at 2 mA, while the four return electrodes placed 3.5 cm apart from the anodal electrode were programmed to −0.5 mA. The previous study anticipated that −0.25 mA inhibitory input from the surrounding cortical areas may negate or override the focalized 1 mA current intensity over M1, which may influence overall M1 excitability (Pellegrini et al, 2020 ). Thus, the improvements in foot physical performance induced by anodal HD-tDCS may not be significant (Xiao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Positive outcomes of HD-tDCS were also reported in previous studies, displaying enhancement in cortical excitability [15], functional connectivity [16], and attention [17] in healthy subjects. In contrast, a number of studies revealed that there was no change in both cortical excitatory in healthy subjects [18] and motor performance in stroke patients [19]. Therefore, it is highly desired to develop alternative strategies for improving neuroplasticity and enhancing motor learning.…”
Section: Introductionmentioning
confidence: 98%